2013
DOI: 10.24036/02013211268-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Komunikasi Interpersonal Antar Siswa Di Sekolah Dan Implikasinya Terhadap Pelayanan Bimbingan Dan Konseling

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
2
0
12
Order By: Relevance
“…One of the services that could be implemented to improve and develop interpersonal communication is a service of the information and guidance of the group. This is in accordance with the research conducted by Sukma & Pratiwi (2013) revealed that the information and guidance of the group is applied to students can enhance interpersonal communication students toward good.…”
Section: Interpersonal Communication Regression Coefficient Test On Psupporting
confidence: 91%
“…One of the services that could be implemented to improve and develop interpersonal communication is a service of the information and guidance of the group. This is in accordance with the research conducted by Sukma & Pratiwi (2013) revealed that the information and guidance of the group is applied to students can enhance interpersonal communication students toward good.…”
Section: Interpersonal Communication Regression Coefficient Test On Psupporting
confidence: 91%
“…Komunikasi interpersonal adalah pertukaran pesan di antara orang, dengan sebuah "pesan" menjadi perilaku orang lain, yang dimaksudkan atau tidak, dapat diinterpretasikan oleh seorang penerima tanpa batasan tentang jumlah orang yang terlibat pertukaran tersebut. Komunikasi interpersonal merupakan suatu perantara atau alat pendukung dalam bentuk bahasa lisan, bahasa tulisan, bahasa tubuh, dan lain-lain sehingga isi komunikasi dapat dipahami oleh penerima pesan (Pratiwi & Sukma, 2013). Uraian tentang individu yang saling berkomunikasi dalam lingkungannya akhirnya menjadi media fardhu bagi manusia untuk menyampaikan idenya (Supratman, 2016).…”
Section: Pendahuluanunclassified
“…Komunikasi interpersonal adalah pertukaran pesan di antara orang, dengan sebuah "pesan" menjadi perilaku orang lain, yang dimaksudkan atau tidak, dapat diinterpretasikan oleh seorang penerima tanpa batasan tentang jumlah orang yang terlibat pertukaran tersebut. Komunikasi interpersonal merupakan suatu perantara atau alat pendukung dalam bentuk bahasa lisan, bahasa tulisan, bahasa tubuh, dan lain-lain sehingga isi komunikasi dapat dipahami oleh penerima pesan (Pratiwi & Sukma, 2013).…”
Section: Pendahuluanunclassified